Sodium-induced calcium release from mitochondria in brown adipose tissue. - Al-Shaikhaly, M H (1979)
Coupled mitochondria of brown adipose tissue can accumulate Ca2+ if a substrate is present. The Ca2+ is released by addition of 20 mM Na+, but not by addition of K+ or choline +. Energy-dissipating Na+-induced Ca2+ cycling occurs maximally with 20 mM Na+ and 10 microM Ca2+. In brown adipocytes, the Ca2+ ionophore A23187 and the Na+ ionophore monensin increase respiration if substrate is added, and incubation in a low-Na+ buffer decreases norepinephrine-induced respiration. Thus Na+-induced Ca2+ release takes place in brown adipose tissue; released Ca2+ could have a regulatory or thermogenic role or both.